PENGARUH JARAK TANAM DAN PEMANGKASAN PUCUK (TOPPING) TERHADAP PERTUMBUHAN DAN PRODUKSI MENTIMUN (Cucumis sativus L.) - Mustopa, Tarwa; Supriyono, Supriyono; Sunarlin, Mochamad Rizki (Jurnal Ilmiah Hijau Cendekia, 2026)
The increase in cucumber plant production is still not optimal due to inappropriate cultivation techniques..The main problem is competition between plants that can be managed through the arrangement of ideal planting distances, as well as the diversion of plant energy for fruit formation that can be optimized through pruning shoots (topping). This research was conducted in Wonorejo Trisulo Village, Kediri, using a factorial randomized block design (RAK) method with two main factors: planting distance with three levels (J1: 40 cm x 50 cm; J2: 40 cm x 60 cm; and J3: 40 cm x 70 cm), and pruning shoots with three levels (P1: after 5 true leaves; P2: after 8 true leaves; P3: after 11 true leaves). The variables observed were the time of the first flower appearance, the number and weight of fruit per plant, the length and diameter of the fruit. The results showed an interaction with the variable number of fruits per plant with the highest average (J3P1). In the J3 planting distance treatment, the results of the influence of fruit weight per plant with an average of 3.7 kg. fruit length at 36 hst, 38 hst, 40 hst, and 42 hst. Fruit diameter at 34 hst, 36 hst, 40 hst, 42 hst. And 44 hst. The treatment of pruning the resulting shoots affected the flowering age, namely the P2 treatment with an average value of 24,2 hst.